# Equivalence of Definitions of Euler's Number

This page has been identified as a candidate for refactoring of medium complexity.We do not want Proof 1 and Proof 2 here. Instead, each of the subproofs is to be made modules of the one overall proof and multiplicated accordingly.Until this has been finished, please leave
`{{Refactor}}` in the code.
Because of the underlying complexity of the work needed, it is recommended that you do not embark on a refactoring task until you have become familiar with the structural nature of pages of $\mathsf{Pr} \infty \mathsf{fWiki}$.To discuss this page in more detail, feel free to use the talk page.When this work has been completed, you may remove this instance of `{{Refactor}}` from the code. |

## Theorem

The following definitions of the concept of **Euler's Number** are equivalent:

### Limit of Series

The series $\ds \sum_{n \mathop = 0}^\infty \frac 1 {n!}$ converges to a limit.

This limit is Euler's number $e$.

### Limit of Sequence

The sequence $\sequence {x_n}$ defined as $x_n = \paren {1 + \dfrac 1 n}^n$ converges to a limit as $n$ increases without bound.

That limit is called **Euler's Number** and is denoted $e$.

### Base of Logarithm

The number $e$ can be defined as the number satisfied by:

- $\ln e = 1$

where $\ln e$ denotes the natural logarithm of $e$.

That $e$ is unique follows from Logarithm is Strictly Increasing.

### Exponential Function

The number $e$ can be defined as the number satisfied by:

- $e := \exp 1 = e^1$

where $\exp 1$ denotes the exponential function of $1$.

## Proof 1

See Equivalence of Definitions of Real Exponential Function: Inverse of Natural Logarithm implies Limit of Sequence for how $\ds \lim_{n \mathop \to \infty} \paren {1 + \frac 1 n}^n = e$ follows from the definition of $e$ as the number satisfied by $\ln e = 1$.

See Euler's Number: Limit of Sequence implies Limit of Series for how $\ds e = \sum_{n \mathop = 0}^\infty \frac 1 {n!}$ follows from $\ds \lim_{n \mathop \to \infty} \paren {1 + \frac 1 n}^n = e$.

Now suppose $e$ is defined as $\ds e = \sum_{n \mathop = 0}^\infty \frac 1 {n!}$.

Let us consider the series $\ds \map f x = \sum_{n \mathop = 0}^\infty \frac {x^n} {n!}$.

From Series of Power over Factorial Converges, this is convergent for all $x$.

We differentiate $\map f x$ with respect to $x$ term by term (justified by Power Series is Differentiable on Interval of Convergence), and get:

\(\ds \map {D_x} {\map f x}\) | \(=\) | \(\ds \map {D_x} 1 + \map {D_x} {\frac x {1!} } + \map {D_x} {\frac {x^2} {2!} } + \map {D_x} {\frac {x^3} {3!} } + \cdots + \map {D_x} {\frac {x^n} {n!} } + \map {D_x} {\frac {x^{n + 1} } {\paren {n + 1}!} } + \cdots\) | ||||||||||||

\(\ds \) | \(=\) | \(\ds 0 + 1 + \frac {2 x} {2!} + \frac {3 x^2} {3!} + \cdots + \frac {n x^{n - 1} } {n!} + \frac {\paren {n + 1} x^n} {\paren {n + 1}!} + \cdots\) | ||||||||||||

\(\ds \) | \(=\) | \(\ds 1 + \frac x {1!} + \frac {x^2} {2!} + \cdots + \frac {x^{n - 1} } {\paren {n - 1}!} + \frac {x^n} {n!} \cdots\) | ||||||||||||

\(\ds \) | \(=\) | \(\ds \map f x\) |

Thus we have:

- $\map {D_x} {\map f x} = \map f x$

From Derivative of Exponential Function:

- $\map f x = e^x$

From Derivative of Inverse Function:

- $\map {D_x} {\map {f^{-1} } x} = \dfrac 1 {\map {f^{-1} } x}$

Hence from Derivative of Natural Logarithm Function:

- $\map {f^{-1} } x = \ln x$

It follows that $e$ can be defined as that number such that $\ln e = 1$.

Hence all the definitions of $e$ as given here are equivalent.

$\blacksquare$

## Proof 2

### 1 implies 2

This is proved in Euler's Number: Limit of Sequence implies Limit of Series.

$\Box$

### 2 implies 3

This is proved in Euler's Number: Limit of Sequence implies Base of Logarithm.

$\Box$

### 3 implies 4

Let $e$ be the unique solution to the equation $\ln x = 1$.

We want to show that $\exp 1 = e$, where $\exp$ is the exponential function.

\(\ds \exp 1 = 0\) | \(\leadstoandfrom\) | \(\ds \map \ln {\exp 1} = \ln e\) | Logarithm is Injective | |||||||||||

\(\ds \) | \(\leadstoandfrom\) | \(\ds 1 = \ln e\) | Exponential is Inverse of Logarithm and Inverse of Inverse |

where the final equation holds by hypothesis.

Hence the result.

$\Box$

### 4 implies 1

Let $e = \exp 1$, where $\exp$ denotes the exponential function.

We want to show that:

- $\ds \sum_{n \mathop = 0}^\infty \frac 1 {n!} = e$

- $\ds \sum_{n \mathop = 0}^\infty \frac 1 {n!} = \exp 1$

We also have that $\exp 1 = e$ by hypothesis.

Hence the result.

$\blacksquare$